The Influence of Internal and External Factors on Sukuk Issuance: A Case Study of Bank Muamalat Syariah during the 2014–2023 Period - Gymnastiar, Raihan Firdaus; Mauluddi, Hasbi Assidiki; Syarief, Moch. Edman; Nugraha, Muhamad Arif (Journal of Applied Islamic Economics and Finance, 2025)
This study aims to analyze financial and macroeconomic performance factors, namely Return on Asset (ROA), Debt to Equity Ratio (DER), Inflation, Money Supply, BI Rate on Sukuk Issuance at Bank Muamalat Syariah for the period 2014-2023. The population used in this study is Bank Muamalat Syariah for the period 2014-2023. The number of samples in this study is 10 annual report data from Bank Muamalat Syariah for the period 2014-2023. The sampling technique uses the multiple regression analysis method (Ordinary Least Square) on Bank Muamalat Syariah for the period 2014-2023. The method used is a quantitative method with Eviews 13 software to test the relationship between variables. The results of this study indicate that partially Return on Asset (ROA), Debt to Equity Ratio (DER), Inflation, Money Supply, BI Rate have an effect on Sukuk Issuance.